High-Energy Ultrafast Fiber Laser at 2-m Based on Cb Ni-Metal Organic Framework - Ahmad, Harith; Zaini, Muhammad Khairol Annuar; Mahmoodin, Zulkifli; Mutlu, Saliha; Filiz, Volkan; Yilmaz, Sevil Savaskan; Arsu, Nergis; Lutfi, Mohamad Akmal Mohamad; Thambiratnam, Kavintheran; Ortac, Bulend (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2026)
A new carborane-containing metal-organic framework (Cb Ni-MOF) was synthesized using a high-power laser-assisted method. The material was prepared from Nickel(II) chloride hexahydrate (NiCI2 center dot 6H(2)O) and m-carborane-1,7-dicarboxylic acid (Cb). FTIR spectroscopy-based structural analysis confirmed successful coordination between the carborane carboxylate groups and Ni(II) ions. SEM-based morphological description revealed 200 nm to 1 mu m-sized polyhedral particles, indicating a crystalline and porous nature. TEM images further revealed nanoscale crystallinity with particle diameters around 50 nm, together with single-/polycrystalline structures with identical features. These findings demonstrate that the laser-assisted process is efficient for preparing nano-ordered, highly crystalline Cb-based MOFs. In this work, the generation of a high-performance ultrafast fiber laser system at the 2- mu m wavelength region was demonstrated. The system utilized a passively mode-locked oscillator incorporating a Cb Ni-MOF deposited on an arc-shaped fiber, demonstrating exceptional nonlinear optical properties with 14.1% modulation depth and 11.2 MW/cm(2) saturation intensity. The laser oscillator generated ultrashort pulses with a duration of 1.2 ps at a center wavelength of 1942.9 nm. Using a chirped pulse amplification (CPA) technique with pre-amplification and main amplification stages, the high-power fiber laser achieves remarkable performance characteristics: 8.4 W average output power, 264 fs pulse duration, 433 nJ pulse energy, and 1.64 MW peak power at 19.4 MHz repetition rate. This high-power ultrafast fiber laser system shows significant potential for applications in invasive medical procedures, advanced material processing, and other fields requiring precise and high-intensity laser-matter interactions.
Keywords: Fiber lasers; Laser mode locking; Transmission electron microscopy; Nonlinear optics; Ultrafast optics; Optical fibers; Fiber nonlinear optics; Optical device fabrication; Optical pulse generation; Optical harmonic generation; High-energy ultrafast fiber laser; thulium-doped fiber; metal-organic frameworks; high-power laser-assisted synthesis (LIRS); THULIUM; HOLMIUM; NM; Engineering; Physics; Optics